Analysis of Performance and Noise on an Asymmetric Double-Suction Fan with Non-Uniformity Inlet Conditions - Yougen Huang; Bin Li; Haohui Chen; Weigang Yang; Qianhao Xiao; Jun Wang (Machines, 2025)
Asymmetric double-suction centrifugal fans are commonly employed in home kitchens to remove cooking pollutants, and their performance is critical to maintaining a healthy indoor environment. However, inlet condition variations significantly influence the aerodynamic efficiency and noise levels. This study utilizes a combination of performance testing and a large eddy simulation to analyze the impact of different inlet conditions on the performance curve, impeller outlet pressure pulsation, unsteady flow structures, and sound quality of an asymmetric double-suction centrifugal fan. A non-uniform air distribution at the inlet is proposed to enhance the fan’s aerodynamic and noise characteristics. The findings reveal that when the inlet area is reduced to less than 70% of its fully open state, the aerodynamic performance declines with decreasing intake area. The amplitude of the superimposed blade-passing frequency is minimized when only the left inlet is open; the pressure coefficient’s fluctuation amplitude in the time domain reaches 0.4, with sharpness peaking at 3.1. In the optimized design, the maximum deviation in total pressure efficiency is limited to 1.96%, with loudness reduced by four sones and improved sharpness and roughness. These results provide valuable insights into the design and noise reduction of asymmetric double-suction squirrel-cage fans.